EKSISTENSI INDUSTRI KERUPUK SANJAI DI KECAMATAN MANDIANGIN KOTO SELAYAN - Dirga Indika Harbi; Rahmanelli Rahmanelli (DEPARTEMEN GEOGRAFI FIS UNP, 2019)
This study aims to analyze the existence of the sanjai cracker industry based on 1) capital, 2) raw materials, 3) labor, 4) and marketing, 5) and the distribution patterns of the sanjai industry in Mandiangin District, Koto Selayan, Bukittinggi City. This type of research is quantitative. The study population was 22 industries, 22 research samples. Data collection techniques in total sampling through observation and questionnaires. The data analysis technique used is the percentage and analysis of the nearest neighbor (nearest neighbor analyst). The results of the study found that 1) the sanjai industry capital in Mandiangin Subdistrict, Koto Selayan in one production time was a maximum of Rp. 5,000,000; 2) raw materials used by the Sanjai industry in one production maximum of 500 kilograms; 3) the number of workers employed at one time the production of sanjai is on average 4 people; 4) marketing aspect, sanjai industry entrepreneurs in determining selling prices follow market prices; 5) the distribution pattern of the sanjai industry with the results of the analysis of the nearest neighbors is obtained that, the distribution pattern in the ratio is 0.832676 which means random distribution patterns.